From waste to wealth: a study of concrete recycling in Jordan - Al-Sharif, Mutasem; Geldermans, Bob; Rinke, Mario (Frontiers in Sustainability, 2024)
The construction industry in Jordan plays a pivotal role in the national economy but also generates a significant amount of concrete waste, leading to environmental and health challenges. Current waste management practices involve landfill use and unregulated disposal, demonstrating the country's infrastructural shortcomings in concrete waste handling. Despite the recognised importance of the construction sector and the challenges of concrete waste management, more comprehensive studies need to focus on the practicality and benefits of recycling concrete within a circular economy framework in Jordan. This gap hinders the development of effective strategies that could mitigate environmental impacts, promote sustainability, and leverage economic and social benefits in the construction industry. Given the accelerating urbanisation, increasing environmental awareness, and the pressing need for sustainable development goals, the timing for this study is critical. It aims to catalyse a timely shift towards more sustainable waste management practices that align with global sustainability trends and national priorities. This study aims to fill the knowledge gap regarding the practicality of recycling concrete within a circular economy context in Jordan and explore the hypothesis that adopting circular economy principles can enhance resource efficiency, reduce waste, lower greenhouse gas emissions, foster economic benefits, and create job opportunities within the sector. Methodologically, this research comprises an analysis based on literature, international comparisons, and technical, economic, and ecological explorations of concrete recycling in Jordan. The literature study establishes a foundational understanding of the current waste management landscape, the anticipated benefits of concrete recycling, and the challenges to its implementation. Furthermore, a technical analysis evaluates the quality and applicability of recycled concrete. The indepth examination of Jordan's concrete waste problem highlights the urbanisation challenges, regulatory gaps, and environmental, social, and economic impacts. Barriers, solutions, and recommendations are discussed through an interdisciplinary lens. This integrated approach supports the transition towards a sustainable, environmentally responsible, and economically viable